Bank pricing under oligopsony-oligopoly: Evidence from 103 developing countries - Walid Marrouch; Rima Turk-Ariss (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
We propose a generic oligopsony-oligopoly model to study bank behavior under uncertainty in developing countries. We derive a pricing structure that acknowledges market power in both the deposit and loan markets and identify two theoretical components to the loan rate: a rent extraction component resulting from the interaction between the choke price of loans and prevailing banking structures, and a markup on deposit funding costs that captures the transformation efficiency of financial intermediation. We then test our structural specification with longitudinal data for 103 non-OECD countries and find that both the market structure under uncertainty and the deposit rate matter significantly in pricing. However, the role played by the rent-extraction share in pricing, on average, dominates funding costs in developing countries, and so underscores the importance of market structure in banks? pricing power.
URN:NBN:fi:bof-201408071910
Keywords: C33; G21; L13; 330; intermediation; bank pricing; market structure; uncertainty; developing countries